2013
DOI: 10.1039/c2ay26158h
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the mineral composition of Brazilian rice and evaluation using chemometric techniques

Abstract: The mineral composition of Brazilian rice samples was determined and the data obtained were evaluated using principal component analysis (PCA) and hierarchical cluster analysis (HCA). Nineteen commercial rice samples were analyzed, six being brown, seven parboiled and six white. The elements were determined employing inductively coupled plasma optical emission spectrometry (ICP OES), and the accuracy was confirmed using a certified reference material of rice flour. The PCA showed the formation of three cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Brazilian rice has been monitored concerning organic and traditional cultivation systems (Borges et al, 2015), mineral composition and daily intake (Da Silva Iago, Ana, & da Silva Maria, 2018;Silva & Ferreira, 2013). Da Silva Iago et al (2018) discriminated white, parboiled, and brown rice mostly by essential element content.…”
Section: What To Traced In Rice?mentioning
confidence: 99%
“…Brazilian rice has been monitored concerning organic and traditional cultivation systems (Borges et al, 2015), mineral composition and daily intake (Da Silva Iago, Ana, & da Silva Maria, 2018;Silva & Ferreira, 2013). Da Silva Iago et al (2018) discriminated white, parboiled, and brown rice mostly by essential element content.…”
Section: What To Traced In Rice?mentioning
confidence: 99%
“…In contrast, Denardin et al (2004) reported 44% lower Zn concentration in milled parboiled rice compared to milled non-parboiled rice, without reporting the degree of milling (DOM). Furthermore, two surveys in Brazilian markets showed that Zn concentration in milled parboiled rice was lower compared to milled non-parboiled rice ( Da Silva et al, 2013 , Runge et al, 2019 ). The Fe concentration found by Da Silva et al (2013) was twice as high in milled parboiled rice compared to milled non-parboiled rice, whereas Runge et al (2019) did not find differences between these two types of rice (DOM unreported).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, lower zinc concentration has been reported in milled parboiled rice compared to milled non-parboiled rice from markets in Bangladesh and Brazil. [12][13][14] Taleon et al 3 reported 21-25% higher zinc losses during milling of parboiled rice (7.5-10.0% bran removal and soaked at 20 °C) compared to nonparboiled rice. Up to 44% higher zinc losses were found by Denardin et al 15 in milled parboiled rice obtained from rough rice soaked in hot water (>60 °C) compared to milled non-parboiled rice.…”
Section: Introductionmentioning
confidence: 99%
“…Hence parboiled rice is considered as more nutritious than non‐parboiled rice 10 ‐ 12 . However, lower zinc concentration has been reported in milled parboiled rice compared to milled non‐parboiled rice from markets in Bangladesh and Brazil 12 ‐ 14 . Taleon et al 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation